Environmental and socio-economic aspects of oyster farming and marine shrimp farming in the Northeast Region of Brazil: Environmental and socio-economic aspects of oyster farming and marine shrimp farming in the Northeast Region of Brazil - Oliveira, Josevânia de; de Jesus Andrade, Edilma; Melo e Souza, Rosemeri (Arquivos de Ciências do Mar, 2021)
In this study we aim to identify the environmental and socioeconomic aspects of oyster farming and shrimp farming in the Northeast region of Brazil. The methodology consisted in documentary research and literature review. Between 2013 and 2017 the Northeast region occupied the third position in the production of oysters, mussels and scallop. At the state level, between 2013 and 2016 the state of Bahia was in the first position, and in 2017 Alagoas moved to the first position. In regard to Shrimp farming activity, the Northeast stood out in the first position, being responsible in 2017 for 98,8% of the national production. Between 2013 and 2016 Ceará was the major producer and in 2017 Rio Grande Norte ranked first. Oyster farming and shrimp farming are socioeconomically relevant activities, creating jobs and playing a significant role our economy. However, when these activities are not managed sustainably, they may cause serious environmental problems, such as eutrophication, contamination, alteration of aquatic biodiversity, among others, changing the entire local hydrodynamics and causing ecological imbalance. For the oyster farming and shrimp farming activities to become less impactful and more profitable, it is necessary to search for environmental planning, training courses for producers, an increase in the added value of the product, a reduction in the number of middlemen, technological development, and the creation of new public policies. Keywords: oyster farming, shrimp farming, environmental impacts, socioeconomic value, Brazilian Northeast.